Electrolyte, secondary battery, and device
By adding unsaturated cyclic carbonate and sulfonate additives to the electrolyte of lithium-ion batteries, the electrolyte decomposition problem caused by nickel-cobalt-manganese materials during charging is solved, and the cycle stability and safety of the battery are significantly improved.
Patent Information
- Application Number
- CN202311096987.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-02-28
AI Technical Summary
In existing lithium-ion batteries, nickel-cobalt-manganese materials will cause the decomposition of the electrolyte during charging, reducing the cycle stability and safety of the battery, and commonly used additives cannot effectively inhibit the dissolution of manganese.
By adding unsaturated cyclic carbonate additives and sulfonate additives to the electrolyte, the two can be combined to form a special CEI interface film on the surface of the positive electrode active material of the ternary NCM material, inhibiting the dissolution of Mn and improving electrochemical performance.
It significantly reduces the battery impedance, reduces the interface side reaction between the electrolyte and the positive electrode sheet, improves the circulation performance and high-temperature storage performance, and improves the safety performance of the battery.
Smart Images

Figure CN119542530A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of energy storage materials, and in particular to an electrolyte, a secondary battery and a device. Background Art
[0002] With its many advantages, lithium-ion batteries have quickly occupied the fields of mobile phones, laptops, and even become a key component of various electric vehicles. However, due to the constraints of the theoretical specific capacity of positive and negative electrode materials, the energy density of existing commercial lithium-ion batteries is difficult to exceed 300Wh kg -1 , which limits its application in pure electric vehicles, aerospace, 5G and other fields. Therefore, it is urgent to develop the next generation of high energy density battery systems and high capacity electrode materials to meet the development needs of future society.
[0003] In order to further improve the energy density of lithium-ion batteries, positive electrode materials with higher energy density are continuously developed. Layered positive electrode ternary NCM (nickel cobalt manganese) materials have attracted more and more attention due to their high specific energy, high power, low cost, and environmental friendliness. However, NCM materials are highly oxidizing during the charging process, which will lead to the continuous decomposition of the electrolyte, which will not only reduce the electrochemical cycle stability of the ternary battery, but also cause a series of problems such as battery bloating and increased interface impedance. As the operating temperature of the battery increases, the side reaction will become more intense, and the gas production problem will become more serious, which will greatly reduce the safety of the battery. By adding a small amount of film-forming additives to the electrolyte, the continuous occurrence of side reactions between the electrode and the electrolyte can be simply and effectively blocked, thereby improving the cycle life and safety of the battery.
[0004] Therefore, current electrolytes, secondary batteries and devices still need to be improved. Summary of the invention
[0005] The inventors found that the use of nickel-cobalt-manganese metal oxide (e.g., ternary NCM) as a positive electrode active material has the problem of manganese dissolution. The commonly used solution is to add a certain amount of vinyl carbonate (VC) additives in the electrolyte, but the additives will easily form a thicker solid electrolyte interface film (CEI film) on the surface of the ternary NCM material, reducing the kinetic properties of the positive electrode material, and additives such as fluoroethylene carbonate (FEC) suitable for ternary NCM materials cannot play a role in inhibiting the dissolution of manganese (Mn). Therefore, it is necessary to develop a new electrolyte system that can inhibit the dissolution of Mn in the ternary NCM material without affecting its kinetic properties, which is of great significance. The electrolyte involved in the present application can form a special CEI interface film on the surface of the positive electrode active material of the ternary NCM material by adding unsaturated cyclic carbonate additives and sulfonate additives, and the two are used in combination, which can inhibit the dissolution of Mn in the NCM material and improve the electrochemical properties of the positive electrode active material.
[0006] In one aspect, the present application provides an electrolyte, the electrolyte comprising a lithium salt, a non-aqueous solvent and an additive, wherein the additive comprises an unsaturated cyclic carbonate additive and a sulfonate additive; the unsaturated cyclic carbonate additive comprises at least one of the compounds shown in Formula I:
[0007]
[0008] In Formula I, R0, R1, R2 and R3 are independently selected from hydrogen, fluorine, substituted or unsubstituted C 1~11 Alkyl, substituted or unsubstituted C 1~8 Alkoxy, substituted or unsubstituted C 2~6 Alkenyl, substituted or unsubstituted C 2~6 Alkenyloxy, substituted or unsubstituted C 2~6 Alkynyl, substituted or unsubstituted C 2~6 Alkynyloxy, substituted or unsubstituted C 2~6 Carbonylalkyl, substituted or unsubstituted C 3~8 Cycloalkyl, substituted or unsubstituted C 3~8 Epoxyalkyl, substituted or unsubstituted C 6~12 Aryl or substituted or unsubstituted C 6~12 heteroaryl; said substituted substituent is selected from fluorine;
[0009] The sulfonate additive includes at least one of the compounds shown in Formula II-A and Formula II-B:
[0010]
[0011] In formula II-A and formula II-B, R4, R5, R6 and R7 are independently selected from hydrogen, fluorine, substituted or unsubstituted C 1~11Alkyl, substituted or unsubstituted C 1~8 Alkoxy, substituted or unsubstituted C 2~6 Alkenyl, substituted or unsubstituted C 2~6 Alkenyloxy, substituted or unsubstituted C 2~6 Alkynyl, substituted or unsubstituted C 2~6 Alkynyloxy, substituted or unsubstituted C 3~8 Cycloalkyl, substituted or unsubstituted C 3~8 Epoxyalkyl, substituted or unsubstituted C 6~12 Aryl or substituted or unsubstituted C 6~12 heteroaryl; the substituted substituent is selected from fluorine; Q1 is selected from O, C 1~6 Alkylene or C 2~6 Q2 and Q3 are independently selected from C 1~6 Alkylene or C 2~6 alkenylene;
[0012] Based on the total mass of the electrolyte, the mass percentage of the unsaturated cyclic carbonate additive is P1%, wherein 0.01≤P1≤10.
[0013] Another aspect of the present application provides a secondary battery, wherein the secondary battery includes the above-mentioned electrolyte.
[0014] Another aspect of the present application provides a device, which includes the secondary battery described above.
[0015] The beneficial effects of this application are:
[0016] By using the electrolyte provided by the present application, adding unsaturated cyclic carbonate additives and sulfonate additives at the same time, the battery impedance (DCR) can be significantly reduced. In addition, by combining unsaturated cyclic carbonate additives and sulfonate additives, the interface side reactions between the electrolyte and the positive electrode plate can be reduced, thereby significantly improving the cycle performance and high temperature storage performance of the high-voltage battery. By using the lithium battery provided by the present application, the safety performance of the battery can be greatly improved. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0018] the term:
[0019] For simplicity, only some numerical ranges are specifically claimed herein. However, any lower limit can be combined with any upper limit to form an unrecorded range; and any lower limit can be combined with other lower limits to form an unrecorded range, and any upper limit can be combined with any other upper limit to form an unrecorded range. In addition, each separately claimed point or single value itself can be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unrecorded range.
[0020] In this article, the terms "comprises", "comprising" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.
[0021] In the description herein, unless otherwise specified, “above” or “below” includes the number itself.
[0022] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0023] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single component or multiple components. Item B may include a single component or multiple components. Item C may include a single component or multiple components.
[0024] The term "DCR" refers to the impedance of the battery, which can be specifically the DC internal resistance. After the battery is discharged, the battery voltage will rebound due to the existence of polarization. The impedance test uses the difference between the voltage at the moment before the end of the intermittent discharge and the voltage after the discharge is stabilized to calculate the battery internal resistance.
[0025] The term "C 1~11“Alkyl” includes, but is not limited to, methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, methylcyclopentyl, n-hexyl, isohexyl, cyclohexyl, and the like.
[0026] The term "C 1~8 The term "alkoxy" includes, but is not limited to, methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, isopentyloxy, or n-hexyloxy.
[0027] The term "C 2~6 "Carbonylalkyl" refers to an alkyl group containing a carbonyl [C(=O)] group.
[0028] The term "C 2~6 "Alkenyl" includes but is not limited to ethenyl, propenyl, butenyl, pentenyl or hexenyl, etc.
[0029] The term "C 2~6 "Alkynyl" includes, but is not limited to, ethynyl, propynyl, butynyl, pentynyl or hexynyl, etc.
[0030] The term "C 3~8 "Cycloalkyl" includes, but is not limited to, cyclopropyl, cyclobutyl, cyclopentyl or cyclohexyl.
[0031] The term "C 6~12 "Aryl" includes but is not limited to phenyl or naphthyl.
[0032] The term "substituted or unsubstituted" means that the functional group described after the term may or may not have a substituent. For example, "substituted or unsubstituted C 1-6 "Alkyl" refers to a C 1-6 Alkyl or unsubstituted C 1-6 wherein the number of substituents may be 1 or more than 2, and the substituents include at least one of halogen, alkyl and aryl. It should be understood that when the number of substituents is greater than 1, each substituent may be the same or different.
[0033] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0034] Electrolyte:
[0035] The electrolyte provided in the present application includes a lithium salt, a solvent and an additive, wherein the additive includes an unsaturated cyclic carbonate additive and a sulfonate additive; the unsaturated cyclic carbonate additive includes at least one of the compounds shown in Formula I:
[0036]
[0037] In Formula I, R0, R1, R2 and R3 are independently selected from hydrogen, fluorine, substituted or unsubstituted C 1~11 Alkyl, substituted or unsubstituted C 1~8 Alkoxy, substituted or unsubstituted C 2~6 Alkenyl, substituted or unsubstituted C 2~6 Alkenyloxy, substituted or unsubstituted C 2~6 Alkynyl, substituted or unsubstituted C 2~6 Alkynyloxy, substituted or unsubstituted C 2~6 Carbonylalkyl, substituted or unsubstituted C 3~8 Cycloalkyl, substituted or unsubstituted C 3~8 Epoxyalkyl, substituted or unsubstituted C 6~12 Aryl or substituted or unsubstituted C 6~12 heteroaryl; said substituted substituent is selected from fluorine.
[0038] In the present application, the sulfonate additive includes at least one of the compounds shown in Formula II-A and Formula II-B:
[0039]
[0040] In formula II-A and formula II-B, R4, R5, R6 and R7 are independently selected from hydrogen, fluorine, substituted or unsubstituted C 1~11 Alkyl, substituted or unsubstituted C 1~8 Alkoxy, substituted or unsubstituted C 2~6 Alkenyl, substituted or unsubstituted C 2~6 Alkenyloxy, substituted or unsubstituted C 2~6 Alkynyl, substituted or unsubstituted C 2~6 Alkynyloxy, substituted or unsubstituted C 3~8 Cycloalkyl, substituted or unsubstituted C 3~8 Epoxyalkyl, substituted or unsubstituted C 6~12 Aryl or substituted or unsubstituted C 6~12 heteroaryl; the substituted substituent is selected from fluorine; Q1 is selected from O, C 1~6 Alkylene or C 2~6 Q2 and Q3 are independently selected from C 1~6 Alkylene or C 2~6 Alkenylene.
[0041] In the present application, the unsaturated cyclic carbonate additive represented by formula I can achieve partial or complete replacement of vinylene carbonate. The unsaturated cyclic carbonate additive represented by formula I is an unsaturated six-membered cyclic carbonate additive, which can form a suitable interface passivation film CEI on the surface of the positive electrode of the battery, which can effectively inhibit the dissolution of Mn in the ternary NCM material without affecting its kinetic properties.
[0042] In the present application, the sulfonate additive represented by formula II-A and / or formula II-B is beneficial to improving the high temperature performance of the battery. It has strong oxidation resistance, so it is beneficial to improve the electrochemical window of the electrolyte, improve the cycle stability and high temperature storage performance of the positive electrode sheet, and can improve the kinetic properties of the positive electrode material.
[0043] In the present application, sulfonate compounds have a greater effect on the positive electrode plate, but their film-forming properties on the surface of the negative electrode plate are average; while the unsaturated cyclic carbonate additive has a better film-forming property on the negative electrode plate side, and also has a good film-forming property on the positive electrode plate, but the film-forming resistance on the positive electrode plate is relatively large; and the combination of unsaturated cyclic carbonate additives and sulfonate additives can improve the dynamic performance and high-temperature performance of the positive electrode plate, so the two have a synergistic effect.
[0044] Thus, by using the electrolyte provided by the present application, adding unsaturated cyclic carbonate additives and sulfonate additives at the same time, the battery impedance (DCR) can be significantly reduced. In addition, by combining unsaturated cyclic carbonate additives and sulfonate additives, the interface side reactions between the electrolyte and the positive electrode plate can be reduced, thereby significantly improving the cycle performance and high temperature storage performance of the high-voltage battery. By using the lithium battery provided by the present application, the safety performance of the battery can be greatly improved.
[0045] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the unsaturated cyclic carbonate additive is P1%, wherein 0.01≤P1≤10. In some embodiments, P1 is 0.01, 0.05, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or any value therebetween. In some embodiments, 1≤P1≤3. When the mass percentage of the unsaturated cyclic carbonate additive is too high, the viscosity of the electrolyte will increase, the conductivity will decrease, and the battery impedance will increase; when the mass percentage of the unsaturated cyclic carbonate additive is too low, it will not effectively inhibit the dissolution of Mn in the ternary NCM material, and will not protect the positive electrode.
[0046] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the sulfonate additive is P2%, wherein 0.01≤P2≤5. In some embodiments, P2 is 0.01, 0.05, 0.1, 0.5, 1, 2, 3, 4, 5 or any value therebetween. In some embodiments, 0.5≤P2≤1.5. When the mass percentage of the sulfonate additive is too high, the viscosity of the electrolyte will increase and the conductivity will decrease; when the mass percentage of the sulfonate additive is too low, the electrode will not be effectively protected at the interface and the battery cycle life will be reduced.
[0047] In some embodiments, 0.5≤P1×P2≤5. P1×P2 is 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.4, 4.6, 4.8, 5 or a range consisting of any two of the above values. In some embodiments, 1≤P1×P2≤3. Thus, by controlling the product of the content of the unsaturated cyclic carbonate additive and the sulfonate additive, the high temperature cycle performance and kinetic performance of the battery can be effectively improved, and the high temperature gas production of the battery can be reduced. When P1×P2 is too large, the battery impedance will increase and the life will be reduced; when P1×P2 is too small, the high temperature performance of the battery will deteriorate, and the positive electrode sheet will not be protected.
[0048] In some embodiments, in Formula I, R0, R1, R2 and R3 are independently selected from hydrogen, fluorine, C 1~6 Alkyl, fluorine-substituted C 1~6 Alkyl, C 2~4 Alkenyl, fluorine-substituted C 2~4 Alkenyl, C 2~4 Carbonylalkyl, fluorine-substituted C 2~4 Carbonyl alkyl, C 6~12 Aryl or fluorine-substituted C 6~12 Aryl.
[0049] In some embodiments, in Formula II-A and Formula II-B, R4, R5, R6 and R7 are independently selected from hydrogen, fluorine, C 1~6 Alkyl, fluorine-substituted C 1~6 Alkyl, C 2~4 Alkenyl, fluorine-substituted C 2~4 Alkenyl, C 6~12 Aryl or fluorine-substituted C 6~12 Aryl; Q1 is selected from O, C 1~4 Alkylene or C 2~4 Q2 and Q3 are independently selected from C 1~4 Alkylene or C 2~4 Alkenylene.
[0050] In some preferred embodiments, the unsaturated cyclic carbonate additive includes at least one of the following compounds:
[0051]
[0052] In some preferred embodiments, the sulfonate additive includes at least one of the following compounds:
[0053]
[0054] Among them, compound II-1 is 1,3-propane sultone (PS), compound II-2 is methylene disulfonate (MMDS), compound II-3 is diethylene sulfate (DTD), compound II-4 is 1,3-propene sultone (1,3-PST), and compound II-5 is 1,4-butane sultone (1,4-BS).
[0055] In some embodiments, the electrolyte further includes a first additive, the first additive including at least one of fluoroethylene carbonate (FEC), vinyl ethylene carbonate, vinyl sulfite, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, succinonitrile, adiponitrile, glutaronitrile and hexanetrinitrile.
[0056] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the first additive is 0.01% to 10%.
[0057] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bisfluorosulfonyl imide, lithium tetrafluoroborate, lithium trifluorosulfonyl, lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium bis(oxalatoborate), lithium bis(fluoromalonate)borate, lithium 4,5-dicyano-2-(trifluoromethyl)imidazole) and lithium difluorooxalatoborate.
[0058] In some embodiments, the concentration of the lithium salt is 0.1 mol / L to 2 mol / L based on the total mass of the electrolyte.
[0059] In some embodiments, the solvent includes at least one of a linear carbonate, a saturated cyclic carbonate and a carboxylic acid ester; wherein the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate and a fluorinated linear carbonate; the saturated cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate and a fluorinated saturated cyclic carbonate; the carboxylic acid ester includes at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone and a fluorinated carboxylic acid ester.
[0060] In some embodiments, the mass percentage of the solvent is 10% to 80% based on the total mass of the electrolyte.
[0061] Secondary battery:
[0062] The secondary battery provided in the present application includes a positive electrode plate, a negative electrode plate and the electrolyte described above. The positive electrode plate includes a positive electrode current collector and a positive electrode active material disposed on the positive electrode current collector. The positive electrode active material includes a compound that reversibly embeds and deintercalates lithium ions. The positive electrode active material may include a composite oxide containing lithium and at least one element selected from cobalt, manganese and nickel. The specific types of positive electrode active materials are not subject to specific restrictions and can be selected according to needs.
[0063] In some embodiments, the positive electrode active material of the positive electrode active material layer includes at least one of lithium nickel transition metal oxides.
[0064] In some embodiments, the lithium nickel transition metal oxide comprises LiNi a Mn b A (1-a-b) At least one of O2 materials, A includes at least one of cobalt, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0.1≤a≤1, 0.1≤b≤1, a+b≤1. In some embodiments, the positive electrode active material includes at least one of lithium nickel cobalt manganese oxide and lithium nickel manganese cobalt magnesium oxide. In some embodiments, the positive electrode active material includes at least one of NCM111, NCM523, NCM622, and NCM811.
[0065] In some embodiments, the positive electrode active material may have a coating layer on the surface, or may be mixed with another compound having a coating layer.
[0066] In some embodiments, the coating may include at least one coating element compound selected from an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, and a hydroxycarbonate of a coating element. The compound for the coating may be amorphous or crystalline. The coating element contained in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating may be applied by any method as long as the method does not adversely affect the performance of the positive active material. For example, the method may include any coating method well known to those of ordinary skill in the art, such as spraying, dipping, etc.
[0067] In some embodiments, the positive electrode active material further includes a binder, and optionally a conductive agent. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.
[0068] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0069] In some embodiments, the positive electrode active material includes a conductive agent to impart conductivity to the electrode. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0070] In some embodiments, the positive electrode active material, conductive agent, and binder can be fully stirred and mixed in a solvent system (for example, N-methylpyrrolidone) in a certain proportion, and then coated on the positive electrode collector, dried, and rolled to obtain a positive electrode sheet.
[0071] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.
[0072] In the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material disposed on the negative electrode current collector.
[0073] In the present application, the negative electrode active material includes at least one of a silicon-based material, a carbon-based material, a tin-based material, a phosphorus-based material and metallic lithium. The silicon-based material includes at least one of silicon, a silicon alloy, a silicon oxide compound and a silicon carbon compound, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes and graphene, the tin-based material includes at least one of tin, tin oxide and tin alloy, and the phosphorus-based material includes phosphorus and / or a phosphorus-carbon composite.
[0074] In some embodiments, the negative electrode active material may further include a binder; the binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0075] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, and the like.
[0076] In some embodiments, the negative electrode active material may further include a conductive material so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0077] In some embodiments, the negative electrode active material, conductive agent, and binder can be fully stirred and mixed in a solvent system (for example, deionized water) in a certain proportion, and then coated on the negative electrode collector, dried, and rolled to obtain a negative electrode sheet.
[0078] In some embodiments, the negative electrode material of the present application may also be selected from other materials that can electrochemically absorb and release metal ions such as lithium ions. Specifically, it can be selected from carbonaceous materials, silicon materials, alloy materials, lithium-containing metal oxide materials, etc. They can be used alone or in any combination of two or more.
[0079] In some embodiments, the negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0080] In the present application, a secondary battery and a device are provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator involved in the present application are not particularly limited, and it can be any technology applied in the prior art.
[0081] In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0082] In some embodiments, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide.
[0083] In some embodiments, the separator may be selected from polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyimide membrane or a multilayer composite membrane thereof, or a composite membrane modified by a ceramic material coating.
[0084] In some embodiments, the impedance of the secondary battery is S mΩ, wherein 0.01≤S≤5. In some embodiments, S is 0.01, 0.05, 0.1, 0.5, 1, 2, 3, 4, 5, or any value therebetween. In some embodiments, 0.5≤S≤3.5. When the impedance is too large, the battery dynamics will be affected, the charge and discharge polarization will increase, the side reactions will be enhanced, and the battery life will be reduced.
[0085] In some embodiments, the porosity of the positive electrode sheet is 15% to 40%. In some embodiments, the porosity of the positive electrode sheet is 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% or any value therebetween. In some embodiments, the porosity of the positive electrode sheet is 27% to 32%. In the present application, the positive electrode porosity can be adjusted according to the characteristics of the selected active material by conventional technical means in the art, such as controlling the rolling pressure, rolling temperature, and rolling speed of the electrode sheet.
[0086] In some embodiments, the porosity of the negative electrode sheet is 20% to 50%. In some embodiments, the porosity of the negative electrode sheet is 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 42%, 44%, 46%, 48%, 50% or any value therebetween. In some embodiments, the porosity of the negative electrode sheet is 30% to 40%. In the present application, the negative electrode porosity can be adjusted according to the characteristics of the selected active material by conventional technical means in the art, such as controlling the rolling pressure, rolling temperature, and rolling speed of the electrode sheet.
[0087] In some embodiments, the secondary battery involved in the present application is made by stacking the above-mentioned positive and negative electrode sheets.
[0088] In some embodiments, the secondary battery involved in the present application may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0089] In some embodiments, a battery module is also provided. The battery module includes the above-mentioned secondary battery. The battery module of the present application may include multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0090] In some embodiments, a battery pack is provided, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0091] Device:
[0092] The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module and battery pack.
[0093] In some embodiments of the present application, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of lithium batteries, a battery pack or battery module may be used.
[0094] In other embodiments of the present application, the device may be a mobile phone, a tablet computer, a laptop computer, etc.
[0095] The present application is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.
[0096] Examples and Comparative Examples
[0097] Example 1
[0098] (1) Preparation of electrolyte:
[0099] In a glove box filled with argon (H2O <0.1ppm, O2 <0.1ppm), ethylene carbonate, propylene carbonate, diethyl carbonate and ethyl methyl carbonate were mixed in a mass ratio of EC:DEC:EMC = 25:20:55, and then 17% of LiPF6 based on the total weight of the electrolyte was slowly added to the mixed solution, and finally 2% of compound I-1 based on the total weight of the electrolyte and 1% of compound II-1 (PS) based on the total weight of the electrolyte were added, and the lithium ion battery electrolyte of Example 1 was obtained after stirring.
[0100] (2) Preparation of positive electrode sheet:
[0101] The positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 O2, conductive agent carbon nanotube / acetylene black (CNT / Super-P), binder polyvinylidene fluoride PVDF, by weight proportion LiNi 0.9Co 0.05 Mn 0.05 O2:CNT / Super-P:PVDF=95:2.0 / 1.0:2, after being fully homogenized in N-methylpyrrolidone (NMP) solvent system, it is coated on the surface of 12μm thick aluminum current collector, and then dried and roll-pressed to obtain the positive electrode sheet.
[0102] (3) Preparation of negative electrode sheet:
[0103] The negative electrode active material artificial graphite, conductive agent acetylene black, binder styrene butadiene rubber SBR, thickener sodium carboxymethyl cellulose CMCNa, and polyacrylic acid PAA are fully slurried in a deionized water solvent in a weight ratio of 95:2:1.5:1:0.5, coated on the surface of a 8 μm thick copper current collector, and then dried, rolled and stripped to obtain a negative electrode sheet.
[0104] (4) Preparation of lithium batteries:
[0105] The prepared positive electrode sheet, separator (PP / PE / PP three-layer composite separator), and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets, and wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic film outer packaging, and the prepared electrolyte is injected into the fully dried artificial graphite / LiNi 0.9 Co 0.05 Mn 0.05 In the O2 battery, the battery is placed at 45°C, formed in a high-temperature fixture (the formation conditions are: temperature 45°C, pressure 210kgf, 0.05C current charging to 4.25V and standing for 60 minutes, then 0.1C charging to 4.25V, and then 0.2C discharge to 3.0V, and this is repeated three times) and secondary sealing, and then conventional capacity division is carried out.
[0106] Examples 2 to 17 and Comparative Examples 1 to 9
[0107] The only difference between Examples 2 to 14 and Comparative Examples 1 to 9 and Example 1 is that at least one of the type and mass percentage of the unsaturated cyclic carbonate additive, the type and mass percentage of the sulfonate additive, the type and mass percentage of the lithium salt, and the type and mass percentage of the first additive in the electrolyte is changed.
[0108] The rest of the preparation methods of Examples 2 to 14 and Comparative Examples 1 to 9 are the same as those of Example 1. Specific adjustment measures and detailed data are shown in Table 1.
[0109] Table 1
[0110]
[0111]
[0112] Test Method
[0113] 1. Impedance (DCR) test:
[0114] Before the cycle capacity retention rate test, the lithium-ion battery was discharged to 2.5V at 1C constant current at 25±2℃, then charged to 4.25V at 0.5C constant current, and charged to 0.05C at 4.25V, and then discharged to 50% SOC at 1C constant current, and left to stand for 60 minutes, and the voltage U1 after the end of the standing was recorded, and then discharged at 2C constant current for 10s, and the voltage U2 after the discharge was recorded, and the 2C current was recorded as I, and left to stand for 60 minutes. According to the formula DCR = (U1-U2) / I, the discharge DCR (impedance) of the battery at 50% SOC is calculated.
[0115] 2. Inductively coupled plasma emission spectrometer (ICP) test:
[0116] After 100 cycles, disassemble the battery, take the negative electrode, scrape the surface active material of the negative electrode, accurately weigh 0.1g powder in a 50mL quartz beaker, add 4.0mL aqua regia, cover with a watch glass, place on an electric stove, heat at low temperature to slightly boil and dissolve for 15 minutes, then remove and cool. Transfer to a 50mL plastic volumetric flask and shake well. Shake the test solution thoroughly before determination, let it stand for a while, and use ICP to test the Mn element content in the sample in ppm.
[0117] 3. Test of the porosity of the electrode:
[0118] The porosity is measured by a mercury intrusion instrument, specifically: the dried electrode sample is cut into thin strips of a certain size, and the apparent volume of the electrode coating is measured using a micrometer, and the apparent volume = sample coating thickness × sample length × sample width. The electrode is then vacuum degassed, rolled up and placed in a sample pool, and the sample volume must be 40% to 70% of the effective volume of the sample tube to ensure measurement accuracy. The pore volume of the sample is then measured using a mercury intrusion instrument, that is, the volume of mercury pressed into the sample, and the porosity = pore volume / apparent volume.
[0119] 4. Cycle capacity retention rate test:
[0120] At 25°C, the lithium-ion battery was charged to 4.25V at 1C constant current and constant voltage, and then discharged to 2.5V at 1C constant current. After 500 cycles of charge and discharge, the capacity retention rate after the 500th cycle at 25°C was calculated according to the following formula: discharge capacity after the 500th cycle / discharge capacity in the first cycle×100%.
[0121] At 25°C, the lithium-ion battery was charged to 4.25V at 2C constant current and constant voltage, and then discharged to 2.5V at 2C constant current. After 200 cycles of charge and discharge, the capacity retention rate after the 200th cycle at 25°C was calculated according to the following formula: discharge capacity after the 200th cycle / discharge capacity in the first cycle×100%.
[0122] At 45°C, the lithium-ion battery was charged to 4.25V at 1C constant current and constant voltage, and then discharged to 2.5V at 1C constant current. After 500 cycles of charge and discharge, the capacity retention rate after the 500th cycle at 45°C was calculated according to the following formula: discharge capacity after the 500th cycle / discharge capacity in the first cycle × 100%.
[0123] 5. Test of storage capacity retention rate at 45℃:
[0124] The battery was charged to 4.25V at 0.5C at 25°C, and then discharged to 2.5V at 0.5C. The discharge capacity of the battery was recorded as a1. The battery was charged to 4.25V at 0.5C at 25°C, and then placed in an oven and stored at 45°C for 7 days. After 7 days of testing, it was taken out of the oven and discharged to 2.5V at 0.5C at 25°C. The discharge capacity of the battery was recorded as b1. The calculation formula for the capacity retention rate after 7 days of storage at 45°C is: (a1-b1) / a1×100%.
[0125] Electrochemical testing:
[0126] Examples 1 to 14 and Comparative Examples 1 to 9 were subjected to electrochemical tests, and the results are shown in Table 2 below:
[0127] Table 2
[0128]
[0129]
[0130]
[0131] From the experimental results, referring to the experimental data of Examples 1 to 14 and Comparative Examples 1 to 6, after adding unsaturated cyclic carbonate additives and sulfonate additives to the electrolyte, the impedance of the secondary battery after formation and the Mn element content of the negative electrode sheet are significantly reduced, and the cycle capacity retention rate and storage performance of the secondary battery are also significantly improved. Further, by controlling the content of the unsaturated cyclic carbonate additive and the content of the sulfonate additive to meet the preset relationship, the detected amount of Mn element in the negative electrode sheet can be significantly reduced, indicating that the dissolution of transition metal ions such as Mn ions in the positive electrode sheet is effectively suppressed, the degradation of the positive electrode sheet is avoided, and the dissolution of the transition metal ions embedded in the negative electrode sheet is alleviated to cause damage to the negative electrode sheet, and the stability of the negative electrode sheet is improved, thereby improving the capacity retention rate of the secondary battery as a whole, and the cycle performance of the lithium battery is significantly improved.
[0132] Combined with Comparative Example 1, only the sulfonate additive is added, the Mn element content of the negative electrode sheet is significantly increased, and the dissolution of transition metal ions such as Mn ions in the positive electrode sheet is obvious, which will cause damage to the negative electrode sheet. Combined with Comparative Example 3, only the unsaturated cyclic carbonate additive is added, resulting in increased impedance, poor cycle performance and storage performance. Combined with Comparative Example 2, when the content of the unsaturated cyclic carbonate additive is too high, the content of the unsaturated cyclic carbonate additive and the content of the sulfonate additive do not meet the preset relationship, resulting in a significant increase in the Mn element content of the negative electrode sheet, and the dissolution of transition metal ions such as Mn ions in the positive electrode sheet is obvious, which will cause damage to the negative electrode sheet. Combined with Comparative Examples 4 to 5, when the content of the sulfonate additive is too high, or the content of the unsaturated cyclic carbonate additive and the content of the sulfonate additive do not meet the preset relationship, resulting in increased impedance, poor cycle performance and storage performance. In combination with Comparative Example 6, when the content of the unsaturated cyclic carbonate additive and the content of the sulfonate additive do not satisfy the preset relationship and are lower than the preset value, the Mn element content of the negative electrode plate increases, and the cycle performance and storage performance are poor.
[0133] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. An electrolyte, characterized in that: The electrolyte comprises a lithium salt, a solvent and an additive, wherein the additive comprises an unsaturated cyclic carbonate additive and a sulfonate additive; The unsaturated cyclic carbonate additive includes at least one of the compounds shown in Formula I: In Formula I, R0, R1, R2 and R3 are independently selected from hydrogen, fluorine, substituted or unsubstituted C 1~11 Alkyl, substituted or unsubstituted C 1~8 Alkoxy, substituted or unsubstituted C 2~6 Alkenyl, substituted or unsubstituted C 2~6 Alkenyloxy, substituted or unsubstituted C 2~6 Alkynyl, substituted or unsubstituted C 2~6 Alkynyloxy, substituted or unsubstituted C 2~6 Carbonylalkyl, substituted or unsubstituted C 3~8 Cycloalkyl, substituted or unsubstituted C 3~8 Epoxyalkyl, substituted or unsubstituted C 6~12 Aryl or substituted or unsubstituted C 6~12 heteroaryl; said substituted substituent is selected from fluorine; The sulfonate additive includes at least one of the compounds shown in Formula II-A and Formula II-B: In formula II-A and formula II-B, R4, R5, R6 and R7 are independently selected from hydrogen, fluorine, substituted or unsubstituted C 1~11 Alkyl, substituted or unsubstituted C 1~8 Alkoxy, substituted or unsubstituted C 2~6 Alkenyl, substituted or unsubstituted C 2~6 Alkenyloxy, substituted or unsubstituted C 2~6 Alkynyl, substituted or unsubstituted C 2~6 Alkynyloxy, substituted or unsubstituted C 3~8 Cycloalkyl, substituted or unsubstituted C 3~8 Epoxyalkyl, substituted or unsubstituted C 6~12 Aryl or substituted or unsubstituted C 6~12 heteroaryl; the substituted substituent is selected from fluorine; Q1 is selected from O, C 1~6 Alkylene or C 2~6 Q2 and Q3 are independently selected from C 1~6 Alkylene or C 2~6 alkenylene; Based on the total mass of the electrolyte, the mass percentage of the unsaturated cyclic carbonate additive is P1%, wherein 0.01≤P1≤10.
2. The electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte, the mass percentage of the sulfonate additive is P2%, wherein 0.01≤P2≤5; and / or 0.5≤P1×P2≤5.
3. The electrolyte according to claim 1 or 2, characterized in that 1≤P1≤3; and / or, 0.5≤P2≤1.5; and / or, 1≤P1×P2≤3.
4. The electrolyte according to claim 1, characterized in that In Formula I, R0, R1, R2 and R3 are independently selected from hydrogen, fluorine, C 1~6 Alkyl, fluorine-substituted C 1~6 Alkyl, C 2~4 Alkenyl, fluorine-substituted C 2~4 Alkenyl, C 2~4 Carbonylalkyl, fluorine-substituted C 2~4 Carbonyl alkyl, C 6~12 Aryl or fluorine-substituted C 6~12 Aryl; and / or In formula II-A and formula II-B, R4, R5, R6 and R7 are independently selected from hydrogen, fluorine, C 1~6 Alkyl, fluorine-substituted C 1~6 Alkyl, C 2~4 Alkenyl, fluorine-substituted C 2~4 Alkenyl, C 6~12 Aryl or fluorine-substituted C 6~12 Aryl; Q1 is selected from O, C 1~4 Alkylene or C 2~4 Q2 and Q3 are independently selected from C 1~4 Alkylene or C 2~4 Alkenylene.
5. The electrolyte according to claim 1, characterized in that The unsaturated cyclic carbonate additive includes at least one of the following compounds: and / or The sulfonate compound includes at least one of the following compounds:
6. The electrolyte according to claim 1, characterized in that The electrolyte also satisfies at least one of the following conditions: (1) The electrolyte further includes a first additive, the first additive including at least one of fluoroethylene carbonate, vinyl ethylene carbonate, vinyl sulfite, tris(trimethylsilyl) phosphate, tris(trimethylsilyl) borate, succinonitrile, adiponitrile, glutaronitrile and hexanetrinitrile; based on the total mass of the electrolyte, the mass percentage of the first additive is 0.01% to 10%; (2) The lithium salt includes lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium trifluorosulfonyl, lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium bis(oxalatoborate), lithium bis(fluoromalonate)borate, lithium 4,5-dicyano-2-(trifluoromethyl)imidazole) and lithium difluorooxalatoborate; the concentration of the lithium salt is 0.1 mol / L to 2 mol / L; and / or The solvent includes at least one of chain carbonates, saturated cyclic carbonates and carboxylates; wherein the chain carbonate includes at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate and fluorinated chain carbonates; the saturated cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate and fluorinated saturated cyclic carbonates; the carboxylates include at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone and fluorinated carboxylates; based on the total mass of the electrolyte, the mass percentage of the solvent is 10% to 80%.
7. A secondary battery, characterized in that: include: A positive electrode sheet, a negative electrode sheet and an electrolyte according to any one of claims 1 to 6.
8. The secondary battery according to claim 7, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector; the positive electrode active material of the positive electrode active material layer comprises at least one of lithium nickel transition metal oxides; the lithium nickel transition metal oxide comprises LiNi a Mn b A (1-a-b) At least one of the O2 materials, A comprises at least one of cobalt, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0.1≤a≤1, 0.1≤b≤1, a+b≤1; and / or The negative electrode plate includes a negative electrode current collector and a negative electrode active material disposed on the negative electrode current collector, wherein the negative electrode active material includes at least one of a silicon-based material, a carbon-based material, a tin-based material, a phosphorus-based material and metallic lithium; wherein the silicon-based material includes at least one of silicon, a silicon alloy, a silicon oxide compound and a silicon-carbon compound, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes and graphene, the tin-based material includes at least one of tin, tin oxide and a tin alloy, and the phosphorus-based material includes phosphorus and / or a phosphorus-carbon composite; and / or The impedance of the secondary battery is SmΩ, wherein 0.01≤S≤5; and / or The porosity of the positive electrode sheet is 15% to 40%; and / or The porosity of the negative electrode plate is 20% to 50%.
9. The secondary battery according to claim 8, characterized in that: 0.5≤S≤3.5。 10. A device, characterized in that: A secondary battery comprising the secondary battery according to claim 8 or 9.